2023
DOI: 10.1002/ejhf.2863
|View full text |Cite
|
Sign up to set email alerts
|

Sodium and potassium changes during decongestion with acetazolamide – A pre‐specified analysis from the ADVOR trial

Abstract: AimsAcetazolamide, an inhibitor of proximal tubular sodium reabsorption, leads to more effective decongestion in acute heart failure (AHF). It is unknown whether acetazolamide alters serum sodium and potassium levels on top of loop diuretics and if baseline values modify the treatment effect of acetazolamide.Methods and resultsThis is a pre‐specified sub‐analysis of the ADVOR trial that randomized 519 patients with AHF and volume overload in a 1:1 ratio to intravenous acetazolamide or matching placebo on top o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…Acetazolamide was not associated with hyponatraemia. Decongestion was improved irrespective of baseline sodium and potassium levels 25 …”
Section: Medical Treatmentmentioning
confidence: 88%
See 1 more Smart Citation
“…Acetazolamide was not associated with hyponatraemia. Decongestion was improved irrespective of baseline sodium and potassium levels 25 …”
Section: Medical Treatmentmentioning
confidence: 88%
“…Decongestion was improved irrespective of baseline sodium and potassium levels. 25 A prospective observational study including 50 patients with acute HF, divided into two groups according to the previous use of furosemide (naïve vs. chronic users), showed that the naïve group had a better diuresis and natriuresis compared to the chronic users. Urine furosemide delivery was similar between groups.…”
Section: Medical Treatment Diureticsmentioning
confidence: 99%
“…However, there was a signal that the moderate rise in serum creatinine that is seen with acetazolamide use during decongestion may be more pronounced in the setting of HF with reduced ejection fraction. Two additional sub-studies found that the benefits of acetazolamide (natriuresis and diuresis) are consistent across the entire range of renal function, and that this medication does not lead to clinically important hypokalemia or hyponatremia [17,18].…”
Section: Maintaining the Spotlight On Congestionmentioning
confidence: 99%
“…In this issue of the Journal, Dhont et al 10 . performed a secondary analysis to elucidate if acetazolamide affects serum sodium and potassium levels when used in conjunction with loop diuretics, and if baseline electrolyte values impact the efficacy and/or safety of acetazolamide.…”
Section: Trial Pharmacotherapy Endpoints Adverse Effects Take Awaymentioning
confidence: 99%
“…), rehospitalization, or all-cause mortality at 3 months. In this issue of the Journal, Dhont et al 10 performed a secondary analysis to elucidate if acetazolamide affects serum sodium and potassium levels when used in conjunction with loop diuretics, and if baseline electrolyte values impact the efficacy and/or safety of acetazolamide. Electrolyte abnormalities frequently accompany decongestion therapy, which is observed due to the mechanism of action of loop diuretics.…”
mentioning
confidence: 99%